First description of the male of Cretaconiopteryx grandis Liu & Lu, 2017 (Neuroptera: Coniopterygidae) from the Cretaceous Burmese amber - Li, Hongyu; Wang, Bo; Liu, Xingyue (Zootaxa, 2019)
The male of Cretaconiopteryx grandis Liu & Lu, 2017, which is the only representative species of the extinct dustywing subfamily Cretaconiopteryginae, is described for the first time from the Upper Cretaceous Burmese amber. The male genitalia, well preserved in the examined specimen, show a number of plesiomorphic characters, which support the sister group relationship between Coniopterygidae and the rest of extant lacewing families.